Measurement of cold challenge responses in primary Raynaud's phenomenon and Raynaud's phenomenon associated with systemic sclerosis. - O'Reilly, D (1992)
Using computed thermography continuous temperature recordings were made before and after cold challenge of the fingers of control subjects and patients with primary Raynaud's phenomenon and Raynaud's phenomenon associated with systemic sclerosis. Basal skin temperature measurements (Tpre) were significantly lower in patients with primary Raynaud's phenomenon and Raynaud's phenomenon associated with systemic sclerosis than in the controls. Temperatures immediately after cold challenge (T0) were significantly lower in patients with primary Raynaud's phenomenon and Raynaud's phenomenon associated with systemic sclerosis than in controls. The lag phase before the start of temperature recovery (Tlag) was significantly greater in patients with primary Raynaud's phenomenon and Raynaud's phenomenon associated with systemic sclerosis than in control subjects. The maximum recovery index (R%) was significantly less in patients with primary Raynaud's phenomenon and Raynaud's phenomenon associated with systemic sclerosis than in controls. The maximum rate of change of temperature during the rapid phase of rewarming (Gmax) was significantly greater in controls than in patients with primary Raynaud's phenomenon and Raynaud's phenomenon associated with systemic sclerosis. Discriminant analysis showed that the dynamic parameters of rewarming (Tlag, Gmax, and R%) showed greater variation between the patients with primary Raynaud's phenomenon and those with Raynaud's phenomenon associated with systemic sclerosis than did Tpre or T0. This method of analysis of cold challenge will be used in studies of the effects of treatment of Raynaud's phenomenon.